3D asymmetrical kinematics of mono-age populations from LAMOST and Gaia common red clump stars. Issue Volume 14:Issue S353(2019) (June 2019) - Wang, H.-F.; López-Corredoira, Martn; Huang, Y.; Carlin, Jeffrey L.
Abstract: With the LAMOST DR4 and Gaia DR2 common red clump giant stars, we investigate the three-dimensional kinematics of Milky Way disk stars in mono-age populations between Galactocentric distances of R = 6 and 15 kpc. We confirm the 3D asymmetrical motions of recent works, and provide time tagging of the Galactic outer disk asymmetrical motions. Radial motions present a north-south asymmetry in the region corresponding to recent density and velocity substructures that were sensitive to the perturbations in the early 6 Gyr. What's more, we discover a new velocity substructure in the north side corresponding to density dip found recently ("south-middle opposite") in the radial and azimuthal velocity. Meanwhile, the vertical velocity with clear vertical bulk motions or bending mode motions has no clear asymmetry corresponding to the in-plane asymmetrical features.